PRINCIPAL'S LEADERSHIP IN BUILDING CHILD-FRIENDLY SCHOOLS BASED ON ORGANIZATIONAL CULTURE IN ELEMENTARY SCHOOLS - Fathul Jannah; Ahmad Suriansyah (JURNAL EDUSCIENCE, 2026)
Purpose - This study aims to analyze the leadership of school principals in building Child-Friendly Schools (CFS) based on organizational culture in elementary schools.Methodology - The study employed a qualitative approach using a case study design at SDN Sungai Miai 10 and SDN Sungai Miai 11 in Banjarmasin. Data were collected through interviews, observations, and documentation involving principals, teachers, students, and educational staff. Data analysis used the interactive model of Miles, Huberman, and Saldana, while data validity was ensured through triangulation of techniques, sources, and time.Findings - The findings revealed that principals acted as agents of organizational culture transformation through strengthening humanistic communication, teacher development, learning supervision, positive discipline, and the habituation of child-oriented school culture. The implementation of a child-friendly organizational culture was reflected in the development of dialogic communication, increased student participation, reduced verbal violence, and more open social relationships between teachers and students. However, the implementation had not yet been fully optimal due to the influence of old cultural patterns, differences in teachers’ understanding, and limitations in strengthening the school institutional system.Contribution - This study concludes that the success of CFS transformation, based on organizational culture, is strongly influenced by the effectiveness of principals’ leadership in continuously internalizing child-friendly values within school culture.